Source node position confidentiality aspects in wireless networks: an extended review. (2016) - Medhane, Darshan Vishwasrao; Sangaiah, Arun Kumar
Position monitoring system (PMS) is one of the applications of wireless networks that aim at monitoring and tracking current position of objects in wireless area. Battlefield surveillance is a classic example of this category in which the soldier needs protection from attackers. The problem here is how to hide and conserve the position of soldier from attacker? Moreover, this problem relates to different circumstances associated with applications like panda hunter game and patient monitoring. Hence, the dilemma lies in giving confidentiality to the source node. This paper, presents a detailed survey of source node position confidentiality (SNPC). We have summarised the solutions that provide SNPC in relation to the attackers' capability. The solutions and research gaps presented in the literature are categorised on the basis of the core techniques used for provision of SNPC and the limitations of the mechanisms stated in literature are addressed.